2018
DOI: 10.1038/s41467-018-07003-5
|View full text |Cite
|
Sign up to set email alerts
|

Sexual rejection via a vomeronasal receptor-triggered limbic circuit

Abstract: Mating drive is balanced by a need to safeguard resources for offspring, yet the neural basis for negative regulation of mating remains poorly understood. In rodents, pheromones critically regulate sexual behavior. Here, we observe suppression of adult female sexual behavior in mice by exocrine gland-secreting peptide 22 (ESP22), a lacrimal protein from juvenile mice. ESP22 activates a dedicated vomeronasal receptor, V2Rp4, and V2Rp4 knockout eliminates ESP22 effects on sexual behavior. Genetic tracing of ESP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 50 publications
(94 reference statements)
0
60
0
Order By: Relevance
“…We saw a very small number of VSNs that were co-activated by BAs and sulfated androgen, estrogen, and pregnanolone ligands, but given the relatively narrow focus of this panel, we cannot exclude that other non-BA steroid ligands may co-activate BA-sensitive VSNs. Overall, these studies show that the VSN sensitivity and selectivity for BAs is comparable to most of the other major known AOS ligand classes (Haga-Yamanaka et al, 2015;Kaur et al, 2014;Leinders-Zufall et al, 2000;Nodari et al, 2008;Osakada et al, 2018).…”
Section: Discussion: Vsns Are Sensitive Selective Ba Detectorsmentioning
confidence: 58%
See 1 more Smart Citation
“…We saw a very small number of VSNs that were co-activated by BAs and sulfated androgen, estrogen, and pregnanolone ligands, but given the relatively narrow focus of this panel, we cannot exclude that other non-BA steroid ligands may co-activate BA-sensitive VSNs. Overall, these studies show that the VSN sensitivity and selectivity for BAs is comparable to most of the other major known AOS ligand classes (Haga-Yamanaka et al, 2015;Kaur et al, 2014;Leinders-Zufall et al, 2000;Nodari et al, 2008;Osakada et al, 2018).…”
Section: Discussion: Vsns Are Sensitive Selective Ba Detectorsmentioning
confidence: 58%
“…Other efforts have explored VNO ligand-receptor interactions using various approaches (Haga-Yamanaka et al, 2015;Isogai et al, 2011;Lee et al, 2019;Stein et al, 2016). Despite recent progress, a small fraction of the VR family has confirmed ligands (Haga-Yamanaka et al, 2014;Haga et al, 2010;Isogai et al, 2011;Isogai et al, 2018;Lee et al, 2019;Osakada et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the same peptide is also responsible for a long-term pheromonal response, namely the Bruce effect, that refers to the pregnancy block in recently pregnant female mice upon exposure to unfamiliar male cues 8,9 . In contrast, a juvenile lacrimal peptide, ESP22, is expressed in 2-to 3-week-old mice and exerts a strong inhibitory effect on adult male mating behavior, also promoting sexual rejection in females 10,11 . Very recently, another lacrimal protein was identified in the male rat that enhances stopping behavior in females 12 .…”
mentioning
confidence: 98%
“…This finding is noteworthy as it infers the presence of pheromonal cues that operate as intraspecific and interspecific signals, at the same time. As for most urinary pheromones, all these lacrimal peptides bind receptors and activate peripheral and central brain areas that are part of the vomeronasal system 7,10,12,13 . No studies have been reported on the physiological and behavioral effects of female tears in the mouse, a species that bases the socio-sexual interactions on pheromones.…”
mentioning
confidence: 99%
“…A third mechanism is a signal that inhibits the inhibition of an excitatory signal. All those mechanisms have been observed in the MASHA (28,29), and the model accommodates all of them. The connections where that variability in the flow of auditory information occurs are the sites that determine the sexual orientation that emerges at puberty.…”
Section: Types Of Involved Connectionsmentioning
confidence: 80%